Diverse school community engagement with the North Carolina active routes to school project: a diffusion study - Seth LaJeunesse; Sam Thompson; Nancy Pullen-Seufert; Mary Bea Kolbe; Stephen Heiny; Cathy Thomas; Edward R. Johnson (BMC, 2019)
Abstract Background Schools located in rural parts of the United States and North Carolina have benefited proportionally less from the federal Safe Routes to School (SRTS) program than their more urban counterparts. We investigated whether and how diverse elementary and middle school communities throughout North Carolina have engaged in a SRTS-inspired, multi-sectoral initiative called the Active Routes to School (ARTS) project over the course of 5 years (2013 through 2017). Methods Analyses included a study sample of 2602 elementary and middle schools in North Carolina, 853 that participated in the ARTS project over the five-year study period and 1749 that had not. Statistical models controlling for county- and school-level confounders predicted schools' involvement in walking and bicycling-promotive events, programs, and policies over time. Results Schools' engagement with ARTS Project programming increased significantly over the study period, with 33% of eligible schools participating with the project by the end of 2017. Participation was most common in promotional events. Such event participation predicted engagement with regularly recurring programming and school- and district-level establishment of biking- and walking-facilitative policies. Lower income schools were more likely to establish recurring bike and walk programs than wealthier schools, whereas rural schools were less likely than city schools to participate in promotional events, yet equally as likely as other schools to participate in recurring bike and walk programs. Conclusions Schools' engagement with the North Carolina ARTS Project diffused despite many schools' rural geographies and lower socioeconomic status. Further, participation in one-time promotional events can portend schools' establishment of recurring walking and biking programs and supportive policies.